A critical examination of the social impacts of large multinational corporations in the age of globalization. Issue 3 (18th October 2019) - Yeganeh, Hamid
Abstract : Purpose: This paper aims to offer a critical examination of the social impacts of large multinational corporations (MNCs) in the age of globalization. Design/methodology/approach: The study adopts a multidisciplinary approach and relies on various scholarly resources in several disciplines including international business, international economics, sociology and international relations. The analysis is organized around eight major areas and constituencies of MNCs including the global scene, workers, competitors, entrepreneurs, government and tax payers, social justice, nations/states and natural environment. Findings: Giant MNCs have benefited from favorable conditions in the past three decades and currently dominate the global scene. In general, the rising corporate profits come not to the benefit, but to the detriment of workers. Large MNCs benefit from their immense resources to develop sophisticated competitive advantages against smaller rivals. They impede small entrepreneurs from scaling up their operations and increasing their market shares. Furthermore, large MNCs often take advantage of their power to shape national and international policies in ways that enable them to enhance their profitability. Overall, large MNCs aggravate the rising economic inequality in different ways, thus contributing to social and financial instability. Furthermore, large MNCs erode state sovereignty and enormously contribute to environmental degradation. Originality/value: While most international business studies focus on the concept of corporate social responsibility or sustainable development, the originality of this paper resides in adopting an alternative perspective and offering a multidisciplinary and critical examination of the social impacts of large MNCs.